C Primer Plus®, Third Edition - Prata, Stephen (Sams, 1998)
The Waite Group's C Primer Plus, Third edition, presents the ANSI C standard beginning with a discussion of the fundamentals of C programming and then continues on to illustrate real-world C programming concepts and techniques. The Waite Group's C Primer Plus, Third Edition, is jam-packed with hundreds of sample programs, challenging yet humorous examples, hints and quizzes. Get the latest information on migrating from C to C++ and find out what will change with the release of the new C ANSI/ISO standard. Learn the mechanics of C programming and how to create programs that are easy to read, debug and update using real-world, easy-to-follow examples.